Aboriginal mothers in prison in Australia: a study of social, emotional and physical wellbeing. (17th April 2019) - Sullivan, Elizabeth A.; Kendall, Sacha; Chang, Sungwon; Baldry, Eileen; Zeki, Reem; Gilles, Marisa; Wilson, Mandy; Butler, Tony; Levy, Michael; Wayland, Sarah; Cullen, Patricia; Jones, Jocelyn; et al.
Abstract: Objective : To describe the social, emotional and physical wellbeing of Aboriginal mothers in prison. Methods : Cross‐sectional survey, including a Short Form Health Survey (SF‐12) and Kessler Psychological Distress Scale (5‐item version) administered to Aboriginal women who self‐identified as mothers. Results : Seventy‐seven Aboriginal mothers in New South Wales (NSW) and 84 in Western Australia (WA) participated in the study. Eighty‐three per cent (n=59) of mothers in NSW were in prison for drug‐related offences, 64.8% (n=46) of mothers in WA were in prison for offences committed under the influence of alcohol. Sixty‐eight per cent (n=52) of mothers in NSW and 35% (n=28) of mothers in WA reported mental health problems. Physical (PCS) and Mental (MCS) component scores of SF‐12 varied for mothers in NSW and WA. Mothers in NSW experienced poorer health and functioning than mothers in WA (NSW: PCS 49.5, MCS 40.6; WA: PCS 54.4, MCS 48.3) and high levels of psychological distress (NSW: 13.1; WA 10.1). Conclusions : Aboriginal mothers in prison have significant health needs associated with physical and mental health, and psychological distress. Implications for public health : Adoption of social and emotional wellbeing as an explanatory framework for culturally secure healthcare in prison is essential to improving health outcomes of Aboriginal mothers in prison in Australia.